Colloidal graphite/graphene nanostructures using collagen showing enhanced thermal conductivity - Bhattacharya S; Dhar P; Das SK; Ganguly R; Webster TJ; Nayar S (International Journal of Nanomedicine, 2014)
Soumya Bhattacharya,1 Purbarun Dhar,2 Sarit K Das,2 Ranjan Ganguly,3 Thomas J Webster,4,5 Suprabha Nayar1 1Biomaterials Group, Materials Science and Technology Division, CSIR-National Metallurgical Laboratory, Jamshedpur, 2Nanofluids, Microfluidics and Bio-MEMS Laboratory, Department of Mechanical Engineering, Indian Institute of Technology-Madras, Chennai, 3Advanced Materials Research and Applications Laboratory, Department of Power Engineering, Jadavpur University, Kolkata, India; 4Department of Chemical Engineering and Program in Bioengineering, Northeastern University, Boston, MA, USA; 5Center of Excellence for Advanced Materials Research, King Abdulaziz University, Jeddah, Saudi Arabia Abstract: In the present study, the exfoliation of natural graphite (GR) directly to colloidal GR/graphene (G) nanostructures using collagen (CL) was studied as a safe and scalable process, akin to numerous natural processes and hence can be termed “biomimetic”. Although the exfoliation and functionalization takes place in just 1 day, it takes about 7 days for the nano GR/G flakes to stabilize. The predominantly aromatic residues of the triple helical CL forms its own special micro and nanoarchitecture in acetic acid dispersions. This, with the help of hydrophobic and electrostatic forces, interacts with GR and breaks it down to nanostructures, forming a stable colloidal dispersion. Surface enhanced Raman spectroscopy, X-ray diffraction, photoluminescence, fluorescence, and X-ray photoelectron spectroscopy of the colloid show the interaction between GR and CL on day 1 and 7. Differential interference contrast images in the liquid state clearly reveal how the GR flakes are entrapped in the CL fibrils, with a corresponding fluorescence image showing the intercalation of CL within GR. Atomic force microscopy of graphene-collagen coated on glass substrates shows an average flake size of 350 nm, and the hexagonal diffraction pattern and thickness contours of the G flakes from transmission electron microscopy confirm ≤ five layers of G. Thermal conductivity of the colloid shows an approximate 17% enhancement for a volume fraction of less than approximately 0.00005 of G. Thus, through the use of CL, this new material and process may improve the use of G in terms of biocompatibility for numerous medical applications that currently employ G, such as internally controlled drug-delivery assisted thermal ablation of carcinoma cells. Keywords: graphene, collagen, colloid, nanostructures, biomimetic, carbon, nanomaterials, heat, thermal ablation, thermal conductivity